Development of new steam engine using the crown cam (1st Report, Design and production of prototype steam engine) - Hidenori KOMATSUBARA; Sadatomo KURIBAYASHI; Koichi HIRATA; Tatsuya OHMACHI (Nihon Kikai Gakkai ronbunshu, 2015)
Most modern transportation vessels are powered by fossil fuels. In recent years, however, as fossil fuels have become depleted and atmospheric pollution by exhaust gases has become a problem, demand has increased for technologies that will allow conservation of fuel and more efficient use of energy. About 35% of the energy in the diesel fuel used by the main engines of large ships is squandered as heat in the exhausts. Other than the power recovered and utilized as a source for superchargers and exhaust gas economizers, almost none of this is being used. If electricity could be generated using these exhaust gases, this would allow shorter operating times for the generating equipment on ships and would contribute to conserving energy there. The authors have begun developing a new version of the steam engine, which, in its conventional form, has employed a grooved cam. However, this steam engine has a maximum output of 60W and its mechanical efficiency is 16%; its output and mechanical efficiency must therefore be raised. The authors' answer to this challenge was to conceive a new type of steam engine using a different cam called a crowned cam. The objective of this study was to develop a steam engine based on a crowned cam that can provide power with low-pressure steam. This report begins with a description of the mechanism and operating principles of the steam engine. This engine uses the crown cam as a motion conversion mechanism to transform linear motion into rotational motion. Next, the overall structure and the design of the prototype are described. Lastly, the prototype engine was tested for its performance in an experiment. The prototype engine showed a power output of 449 W, at which it had a mechanical efficiency of 53%.